2017
DOI: 10.1002/cjce.23045
|View full text |Cite
|
Sign up to set email alerts
|

The effective promotion of trace amount of Cu on Ce/WO3‐ZrO2‐TiO2 monolithic catalyst for the low‐temperature NH3‐SCR of NOx

Abstract: The selective catalytic reduction of NOx with NH3 (NH3‐SCR) activity of 0.10 g/g CeO2/WO3‐ZrO2‐TiO2 (Ce/WZT) in low temperature range was greatly enhanced by the addition of 0.00010 g/g Cu (Cu/Ce mass ratio = 1:1000). The temperature of complete NOx conversion (T90) decreased as much as 36  °C (from 263  °C to 227  °C) under a gas hourly space velocity (GHSV) of 30 000 h−1. XPS, NH3/O2‐TPD, H2‐TPR, XRD, and FTIR characterizations revealed that the interaction between Cu and Ce, more active oxygen species, stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The CHA structure assembled from six-membered rings or eight-membered rings could be confirmed based on the characteristic diffraction peaks (2θ = 9.5, 14, and 16°). The structural characteristic peaks of the samples showed that the framework structures of the catalysts were not damaged . No characteristic peaks (2θ = 35.6 and 38.7°) associated with CuO were found.…”
Section: Results and Discussionmentioning
confidence: 90%
“…The CHA structure assembled from six-membered rings or eight-membered rings could be confirmed based on the characteristic diffraction peaks (2θ = 9.5, 14, and 16°). The structural characteristic peaks of the samples showed that the framework structures of the catalysts were not damaged . No characteristic peaks (2θ = 35.6 and 38.7°) associated with CuO were found.…”
Section: Results and Discussionmentioning
confidence: 90%
“…The Ce 3d spectra are shown in Figure . As illustrated, the peaks denote as v′ and u′ which are assigned to Ce 3+ state, while v, v′′, and v′′′ contribute to Ce 4+ state, indicating that cerium on the surface of graphene was present in two different oxidation states: Ce 4+ and Ce 3+ . In addition, the calculated percentages of Ce 3+ for 2Cu‐3Ce/3DG and 3Ce/3DG catalysts increase from 14.5 % to 15.4 % with added Cu, which is beneficial to form more oxygen vacancy and unsaturated chemical bonds and improve the SCR denitrification performance of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Cu−CeO 2 /WO 3 ‐ZrO 2 ‐TiO 2 binary catalysts and the new type of Cu‐Ce−S nanocrystalline catalysts were prepared by Li et al. and Shi et al., respectively . The results proved the interaction between Cu and Ce, the increase of active oxygen species, the enhancement of redox ability, the abundant acid sites and the synergistic effect of Cu 2+ doping between sulfurization that enhances the catalytic activity of the catalysts and shows excellent resistance to H 2 O and SO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, monolithic catalysts have attracted much attention from both the academic community and industrial sector because of their attractive application such as VOCs combustion, production of hydrogen, selective catalytic reduction of NOx with NH 3 , the Fischer‐Tropsch synthesis, Biodiesel production, and used as efficient reactors . Nowadays, the monolithic catalysts and reactors are regarded as a very promising alternate to conventional pellets or powders, owing to the prominent advantages of low pressure drop, low mass transfer resistance, ease of scale‐up ,, …”
Section: Introductionmentioning
confidence: 99%